Strategi Dakwah dalam Surah Al-Muddatstsir Ayat:1-7 (Analisis Tafsir Sinar Karya Buya Malik Ahmad) - Abdul Basith Muttaqin; Iskandar; Fuad Fansuri; Mursalim (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the characteristics and methodology of Buya Malik Ahmad's interpretation in Tafsir Sinar and to examine the da'wah strategies contained in Surah Al-Muddatstsir verses 1–7. The study is motivated by the importance of understanding Qur'anic da'wah concepts through the perspective of Indonesian tafsir traditions that are relevant to contemporary socio-religious contexts. This research employs a qualitative approach with a library research method. The primary source is Tafsir Sinar by Buya Malik Ahmad, while secondary data were obtained from books, journals, and other relevant literature. Data were collected through documentation techniques and analyzed using descriptive-analytical methods. The findings reveal that Tafsir Sinar applies the tahlili method by integrating bil ma’tsur and bil ra’yi approaches. Its main characteristics include a chronological arrangement based on the order of revelation (tartib al-nuzul), an adabi ijtima’i orientation, an emphasis on the purification of faith, and the use of communicative and contextual language. Furthermore, the da'wah strategies identified in Surah Al-Muddatstsir verses 1–7 consist of six fundamental strategies: proactive and transformative strategy (inzar), theocentric strategy (spiritual superiority), integrity and personality strategy (self-purification), value differentiation strategy (ideological hijrah), sincerity and anti-transactional strategy, and mental resilience strategy. These findings indicate that da'wah in the perspective of Tafsir Sinar is not merely oriented toward conveying religious messages but also emphasizes the development of spiritual, moral, and psychological qualities of preachers as agents of social transformation. Therefore, Buya Malik Ahmad's da'wah thought in Tafsir Sinar contributes significantly to the development of da'wah and Nusantara tafsir studies in the contemporary era.